Electrodeposition preparation method of metal ceramic coating on surface of crystallizer copper plate

Through ultrasonic pulse electrodeposition technology, the metal cermet coating is generated on the surface of the crystallizer copper plate, which solves the problems of low strength and poor coating uniformity in the prior art, and achieves a coating with high hardness, wear resistance and good thermal conductivity, improving the coating with improved The overall performance of the crystallizer copper plate.

CN119433656APending Publication Date: 2025-02-14武汉钢铁有限公司

Patent Information

Application Number
CN202411325630.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-14

Smart Images

  • Figure CN119433656A_ABST
    Figure CN119433656A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of surface coatings, and discloses an electro-deposition preparation method of a crystallizer copper plate surface metal ceramic coating, which comprises the following steps: 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in water, then adding nano powder which comprises nano nickel powder, nano aluminum oxide powder, nano silicon carbide powder and nano zirconium oxide powder, and uniformly mixing the nano nickel powder, the nano aluminum oxide powder, the nano silicon carbide powder and the nano zirconium oxide powder; uniformly dispersing by adopting ultrasonic waves to obtain electrolyte; and (2) placing a nickel sheet serving as an anode and the crystallizer copper plate substrate serving as a cathode in electrolyte, applying ultrasonic waves to the electrolyte, applying pulse current between the two electrodes for electrodeposition, taking out the cathode after deposition, and cleaning and drying to obtain the crystallizer copper plate with a metal ceramic coating on the surface. According to the method, the micron-sized coating is generated on the surface of the crystallizer copper plate through ultrasonic pulse electrodeposition, and the coating is composed of ceramic and metal composite phases and is tightly combined with a crystallizer copper plate base body, so that the wear resistance of the crystallizer copper plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface coatings, and in particular relates to an electrodeposition preparation method for a metal ceramic coating on the surface of a crystallizer copper plate. Background Art

[0002] As one of the core devices of continuous casting production, the copper plate of the crystallizer is subjected to the heat load of high-temperature molten steel, thermal corrosion, and wear and stress caused by the movement of the billet. Therefore, it is very easy to suffer from wear, thermal corrosion, thermal cracking and deformation under harsh service conditions. In order to solve these problems, researchers have proposed many related preparation technologies, mainly through copper alloying and surface treatment technology to improve the performance of the crystallizer. Compared with copper alloying, the use of appropriate surface treatment technology to coat / plate one or several materials on the surface of the copper plate to obtain a special functional surface. While ensuring that its thermal conductivity is not greatly affected by the coating / plating, various coatings / platings that are firmly bonded to the substrate and have good wear resistance can be obtained to improve the surface performance of the copper plate, extend its service life, and improve the quality of the billet, thereby achieving the purpose of reducing the cost of casting a ton of steel.

[0003] The reported surface treatment technologies for crystallizer copper plates are mainly concentrated on surface modification methods such as electroplating, laser cladding and all-ceramic coating crystallizer technology. Each technology has its advantages and disadvantages. The disadvantage of electroplating is that the coating and the substrate are physically bonded rather than metallurgically bonded, and the bonding strength is low. Frequent hot and cold fatigue, impact and friction of molten steel and billet during crystallizer casting often cause the coating to peel off. The main disadvantage of laser cladding is that the structure after cladding is mostly uneven dendritic structure, which requires subsequent heat treatment. The service life of the all-ceramic composite crystallizer is about twice that of the traditional crystallizer, but the price is relatively expensive, and it has not yet been widely promoted and cited. Therefore, it is necessary to develop a crystallizer copper plate surface treatment technology that is tightly bonded to the substrate, has a uniform and dense coating, and can be applied on a large scale. Summary of the invention

[0004] The technical problem to be solved by the present invention is to address the deficiencies in the prior art and to provide an electroplating preparation method for a metal ceramic coating on the surface of a crystallizer copper plate. A layer of micron-level coating is generated on the surface of the crystallizer copper plate by ultrasonic pulse electroplating. The coating is composed of a composite phase of ceramic and metal and is tightly bonded to the crystallizer copper plate substrate, thereby improving the wear resistance of the crystallizer copper plate and the coating also has better thermal conductivity.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a metal ceramic coating on the surface of a crystallizer copper plate by electrodeposition, comprising the following steps:

[0006] 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in water, then adding nano powders, the nano powders comprising nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder, and uniformly dispersing by ultrasonic wave to obtain an electrolyte;

[0007] 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and placed in an electrolyte, ultrasonic waves are applied to the electrolyte, and a pulse current is applied between the two electrodes for electrodeposition. After deposition, the cathode is removed, cleaned and dried to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

[0008] In the above scheme, in the electrolyte, the content of nickel sulfate hexahydrate is 196-350 g / L, the content of nickel chloride hexahydrate is 42-88 g / L, the content of boric acid is 28-35 g / L, and the content of nano powder is 50-100 g / L.

[0009] In the above scheme, in the nano powder, the mass ratio of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder is 3:(1-3):(1-3):(1-3).

[0010] In the above scheme, the purity of the nano nickel powder is greater than 99%, and the particle size is 3-10 nm.

[0011] In the above scheme, the purity of the nano alumina powder is greater than 99.9%, and the particle size is 15 to 30 nm.

[0012] In the above scheme, the purity of the nano silicon carbide powder is greater than 99.9%, and the particle size is 10 to 40 nm.

[0013] In the above scheme, the purity of the nano zirconium oxide powder is greater than 99.9%, and the particle size is 5 to 10 nm.

[0014] In the above scheme, in step 1), the ultrasonic dispersion time is 10 to 18 hours.

[0015] In the above solution, the sum of the nickel and cobalt contents of the nickel sheet is ≥ 99.9%.

[0016] In the above scheme, the copper plate substrate of the crystallizer is Cu-Cr-Zr alloy or Cu-Cr-Zr-Al alloy.

[0017] Furthermore, when the copper plate matrix of the crystallizer is a Cu-Cr-Zr alloy, its chemical composition includes, by mass percentage: 0.05-2.0% Cr, 0.08-0.3% Zr, and the rest Cu and unavoidable impurities.

[0018] Furthermore, when the copper plate matrix of the crystallizer is a Cu-Cr-Zr-Al alloy, its chemical composition includes, by mass percentage: Cr 0.1-2.0%, Zr 0.08-0.4%, Al 0.1%-2.0%, and the rest is Cu and unavoidable impurities.

[0019] In the above scheme, the nickel sheet needs to be pre-treated before use, and the steps include: first, wiping the surface of the nickel sheet with deionized water and acetone repeatedly and alternately, then placing the nickel sheet in a mixed acid solution of nitric acid with a mass concentration of 60-70% and hydrochloric acid with a mass concentration of 36-40% in a mass ratio of 1:(6-8) for 1-5 minutes, taking it out and washing it with deionized water, and placing it in anhydrous ethanol for standby use.

[0020] In the above scheme, the crystallizer copper plate substrate needs to be pre-treated before use, and the steps include: first, the surface of the substrate is polished flat with sandpaper, and then the substrate is ultrasonically cleaned in acetone at 50-55°C for 15-60 minutes, and then placed in anhydrous ethanol for ultrasonic cleaning at room temperature for 15-60 minutes. After cleaning, it is placed in anhydrous ethanol for standby use.

[0021] In the above solution, the distance between the anode and the cathode is 15 to 25 mm.

[0022] In the above scheme, in step 2), the power of the ultrasonic wave is 1.5-1.8 kW and the frequency is 30-40 kHz.

[0023] In the above scheme, the current density of the pulse current is 2-4A / dm, the pulse frequency is 500-3000Hz, and the pulse switching time in each pulse cycle is 0.5-3ms and 20-80ms respectively.

[0024] In the above scheme, the electrolyte temperature is controlled to be 60-80°C during the electrodeposition process.

[0025] In the above scheme, the electrodeposition time is 80 to 150 minutes.

[0026] In the above solution, the thickness of the metal ceramic coating is 5 to 50 μm.

[0027] In the above scheme, the relative density of the metal ceramic coating is greater than 99.7%, the Vickers hardness HV is 350-600, the friction factor is 0.35-0.45, the thermal conductivity is 15-25W / m·K at 700K, and the bonding strength between the coating and the crystallizer copper plate substrate is 170-250MPa.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1) The present invention generates a micron-level coating on the surface of the crystallizer copper plate through ultrasonic pulse electrodeposition. During the ultrasonic pulse electrodeposition process, a composite metal ceramic phase of Ni-Al2O3, Ni-SiC and Ni-ZrO2 is formed, and the ceramic phase in the coating is supported, so that the hardness value of the coating is higher, thereby improving the wear resistance of the crystallizer copper plate. During the electrodeposition process, due to the metal bonding effect of Ni with the crystallizer copper plate substrate, Ni can react with the substrate to generate Ni-Cu or Ni-Cr-Cu bonding phase, thereby greatly improving the bonding performance between the coating and the crystallizer copper plate substrate.

[0030] 2) The pulse electrodeposition of the present invention can avoid the inevitable hydrogen evolution and concentration polarization caused by the continuous deposition of metal ions approaching the cathode during direct current electroplating; during pulse electroplating, when the current is turned on, the metal ions close to the cathode are fully deposited; when the current is turned off, the discharged ions around the cathode return to the initial concentration; in this way, the periodic continuous repeated pulse current is mainly used for the reduction of metal ions, and the existence of the off time is conducive to the recovery of the concentration near the cathode, thereby obtaining a highly densified coating with fewer pores and better thermal conductivity; at the same time, ultrasonic waves are introduced into the electrodeposition, and the cavitation effect of ultrasonic waves can alleviate the agglomeration of nanoparticles, so that the nano-ceramic phase particles are evenly distributed in the coating, and the high-speed micro-jet of ultrasonic waves can also play a strong stirring role, greatly improving the uniformity of the nano-ceramic phase in the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a metallographic micrograph of the metal ceramic coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0033] In the following embodiments, the "GB / T 39688-2020 Test method for density of ceramic coating" is used to test the relative density of the coating; the "GB / T 16534-2009 Test method for room temperature hardness of fine ceramics" is used to test the hardness of the coating; the "GB / T6569-2006 Test method for bending strength of fine ceramics" is used to test the bonding strength between the coating and the crystallizer copper plate substrate; the "GB / T 43853-2024 Ball-disc method for high temperature friction and wear performance test of laser repair layer" is used to test the friction factor of the coating; and the "JC / T 2757-2023 Laser flash method for thermal diffusivity of fine ceramics" is used to test the thermal conductivity of the coating at 700K.

[0034] Example 1

[0035] Preparation:

[0036] 1) Nano powder: nano nickel powder, with a purity of 99.2% and a particle size of 3nm; nano alumina powder, with a purity of 99.95% and a particle size of 25nm; nano silicon carbide powder, with a purity of 99.95% and a particle size of 15nm; nano zirconium oxide powder, with a purity of 99.94% and a particle size of 5nm;

[0037] 2) Crystallizer copper plate substrate: the material is Cu-Cr-Zr alloy, and the chemical composition by mass percentage includes: Cr0.15%, Zr 0.18%, and the rest is Cu and inevitable impurities; pre-treatment is performed before use, and the steps include: first, the substrate surface is polished and smoothed with sandpaper of different particle sizes (400 mesh, 800 mesh and 1200 mesh), and then the substrate surface is ultrasonically cleaned in acetone at 50°C for 20 minutes, and then ultrasonically cleaned in anhydrous ethanol at room temperature for 20 minutes to wash away impurities on the surface of the sample, and the cleaned substrate surface is placed in anhydrous ethanol for standby use to prevent surface oxidation;

[0038] 3) Nickel sheet: the sum of nickel and cobalt content ≥ 99.9%; pretreatment is performed before use, the steps comprising: first wiping the surface of the nickel sheet with deionized water and acetone alternately and repeatedly, then placing the nickel sheet in a mixed acid solution of 65% nitric acid and 37% hydrochloric acid in a mass ratio of 1:7 for 2 minutes, taking out and washing with deionized water, and placing in anhydrous ethanol for standby use;

[0039] The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate of this embodiment by electrodeposition comprises the following steps:

[0040] 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in deionized water, then adding nano powder, wherein the nano powder consists of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder in a mass ratio of 3:1:1:1, and dispersing by ultrasonic for 12 hours to obtain an electrolyte; in the electrolyte, the content of nickel sulfate hexahydrate is 255 g / L, the content of nickel chloride hexahydrate is 47 g / L, the content of boric acid is 30 g / L, and the content of nano powder is 65 g / L;

[0041] 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and is placed in an electrolyte with a distance of 20 mm between the anode and the cathode. Ultrasonic waves are applied to the electrolyte with a power of 1.8 kW and a frequency of 40 kHz. A pulse current is applied between the two electrodes with a current density of 2.5 A / dm and a pulse frequency of 1000 Hz. The pulse switching time in each pulse cycle is 0.5 ms and 30 ms respectively. The electrodeposition is performed for 90 min. The electrolyte temperature is controlled at 65°C during the electrodeposition process. After deposition, the cathode is removed for cleaning and drying to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

[0042] After testing, the thickness of the metal ceramic coating is 25μm, the relative density is 99.8%, the Vickers hardness HV is 455, the friction factor is 0.4, the thermal conductivity is 18W / m·K at 700K, and the bonding strength between the coating and the crystallizer copper plate substrate is 185MPa.

[0043] Figure 1 This is a metallographic micrograph of the metal ceramic coating prepared in Example 1, which shows that the ceramic phase in the coating is evenly dispersed.

[0044] Example 2

[0045] Preparation:

[0046] 1) Nano powder: nano nickel powder, with a purity of 99.5% and a particle size of 8nm; nano alumina powder, with a purity of 99.96% and a particle size of 15nm; nano silicon carbide powder, with a purity of 99.96% and a particle size of 15nm; nano zirconium oxide powder, with a purity of 99.95% and a particle size of 5nm;

[0047] 2) Crystallizer copper plate substrate: the material is Cu-Cr-Zr alloy, and the chemical composition by mass percentage includes: Cr0.15%, Zr 0.1%, and the rest is Cu and inevitable impurities; pre-treatment is performed before use, and the steps include: first, the substrate surface is polished and smoothed with sandpaper of different particle sizes (400 mesh, 800 mesh and 1200 mesh), and then the substrate surface is ultrasonically cleaned in acetone at 52°C for 25 minutes, and then ultrasonically cleaned in anhydrous ethanol at room temperature for 35 minutes to wash away impurities on the surface of the sample, and the cleaned substrate surface is placed in anhydrous ethanol for standby use to prevent surface oxidation;

[0048] 3) Nickel sheet: the sum of nickel and cobalt content ≥ 99.9%; pretreatment is performed before use, the steps comprising: first wiping the surface of the nickel sheet with deionized water and acetone alternately and repeatedly, then placing the nickel sheet in a mixed acid solution of 69% nitric acid and 38% hydrochloric acid in a volume ratio of 1:6 for 3 minutes, taking out and washing with deionized water, and placing in anhydrous ethanol for standby use;

[0049] The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate of this embodiment by electrodeposition comprises the following steps:

[0050] 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in deionized water, then adding nano powder, wherein the nano powder is composed of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder in a mass ratio of 3:2:1:1.5, and dispersing by ultrasonic for 14 hours to obtain an electrolyte; in the electrolyte, the content of nickel sulfate hexahydrate is 288 g / L, the content of nickel chloride hexahydrate is 64 g / L, the content of boric acid is 32 g / L, and the content of nano powder is 75 g / L;

[0051] 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and is placed in an electrolyte with a distance of 18 mm between the anode and the cathode. Ultrasonic waves are applied to the electrolyte with a power of 1.7 kW and a frequency of 35 kHz. A pulse current is applied between the two electrodes with a current density of 3 A / dm and a pulse frequency of 1500 Hz. The pulse switching time in each pulse cycle is 1.0 ms and 40 ms respectively. The electrodeposition is performed for 120 min. The electrolyte temperature is controlled at 70°C during the electrodeposition process. After deposition, the cathode is removed for cleaning and drying to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

[0052] After testing, the thickness of the metal ceramic coating is 35μm, the relative density is 99.8%, the Vickers hardness HV is 550, the friction factor is 0.38, the thermal conductivity is 16W / m·K at 700K, and the bonding strength between the coating and the crystallizer copper plate substrate is 215MPa.

[0053] Example 3

[0054] Preparation:

[0055] 1) Nano powder: nano nickel powder, with a purity of 99.7% and a particle size of 10nm; nano alumina powder, with a purity of 99.98% and a particle size of 15nm; nano silicon carbide powder, with a purity of 99.98% and a particle size of 15nm; nano zirconium oxide powder, with a purity of 99.98% and a particle size of 5nm;

[0056] 2) Crystallizer copper plate substrate: the material is Cu-Cr-Zr-Al alloy, and its chemical composition by mass percentage includes: Cr 0.1%, Zr 0.28%, Al 0.1%, and the rest is Cu and inevitable impurities; pretreatment is performed before use, and the steps include: first, the substrate surface is polished and smoothed with sandpaper of different particle sizes (400 mesh, 800 mesh and 1200 mesh), and then the substrate surface is ultrasonically cleaned in acetone at 54°C for 40 minutes, and then ultrasonically cleaned in anhydrous ethanol at room temperature for 20 minutes to wash away impurities on the surface of the sample, and the cleaned substrate surface is placed in anhydrous ethanol for standby use to prevent surface oxidation;

[0057] 3) Nickel sheet: the sum of nickel and cobalt content is ≥ 99.9%; pretreatment is performed before use, the steps comprising: first wiping the surface of the nickel sheet with deionized water and acetone alternately and repeatedly, then placing the nickel sheet in a mixed acid solution of 65% nitric acid and 37% hydrochloric acid in a volume ratio of 1:8 for 4 minutes, taking out and washing with deionized water, and placing in anhydrous ethanol for standby use;

[0058] The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate of this embodiment by electrodeposition comprises the following steps:

[0059] 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in deionized water, then adding nano powder, wherein the nano powder is composed of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder in a mass ratio of 3:1:2:1, and dispersing by ultrasonic for 16 hours to obtain an electrolyte; in the electrolyte, the content of nickel sulfate hexahydrate is 261 g / L, the content of nickel chloride hexahydrate is 64 g / L, the content of boric acid is 29 g / L, and the content of nano powder is 85 g / L;

[0060] 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and is placed in an electrolyte with a distance of 22 mm between the anode and the cathode. Ultrasonic waves are applied to the electrolyte with a power of 1.75 kW and a frequency of 39 kHz. A pulse current is applied between the two electrodes with a current density of 3.2 A / dm and a pulse frequency of 2000 Hz. The pulse switching time in each pulse cycle is 2 ms and 60 ms respectively. The electrodeposition is performed for 130 min. The electrolyte temperature is controlled at 65°C during the electrodeposition process. After deposition, the cathode is taken out for cleaning and drying to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

[0061] After testing, the thickness of the metal ceramic coating is 45μm, the relative density is 99.9%, the Vickers hardness HV is 585, the friction factor is 0.38, the thermal conductivity is 21W / m·K at 700K, and the bonding strength between the coating and the crystallizer copper plate substrate is 230MPa.

[0062] Example 4

[0063] Preparation:

[0064] 1) Nano powder: nano nickel powder, with a purity of 99.9% and a particle size of 5nm; nano alumina powder, with a purity of 99.97% and a particle size of 15nm; nano silicon carbide powder, with a purity of 99.98% and a particle size of 15nm; nano zirconium oxide powder, with a purity of 99.98% and a particle size of 7nm;

[0065] 2) Crystallizer copper plate substrate: the material is Cu-Cr-Zr-Al alloy, and its chemical composition by mass percentage includes: Cr 0.15%, Zr 0.1%, Al 0.15%, and the rest is Cu and inevitable impurities; pre-treatment is performed before use, and the steps include: first, the substrate surface is polished and smoothed with sandpaper of different particle sizes (400 mesh, 800 mesh and 1200 mesh), and then the substrate surface is ultrasonically cleaned in acetone at 53°C for 45 minutes, and then ultrasonically cleaned in anhydrous ethanol at room temperature for 30 minutes to wash away impurities on the surface of the sample, and the cleaned substrate surface is placed in anhydrous ethanol for standby use to prevent surface oxidation;

[0066] 3) Nickel sheet: the sum of nickel and cobalt content is ≥ 99.9%; pretreatment is performed before use, the steps comprising: first wiping the surface of the nickel sheet with deionized water and acetone alternately and repeatedly, then placing the nickel sheet in a mixed acid solution of 65% nitric acid and 38% hydrochloric acid in a volume ratio of 1:6 for 5 minutes, taking out and washing with deionized water, and placing in anhydrous ethanol for standby use;

[0067] The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate of this embodiment by electrodeposition comprises the following steps:

[0068] 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in deionized water, then adding nano powder, wherein the nano powder is composed of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder in a mass ratio of 3:2:1:2, and dispersing by ultrasonic for 18 hours to obtain an electrolyte; in the electrolyte, the content of nickel sulfate hexahydrate is 289 g / L, the content of nickel chloride hexahydrate is 85 g / L, the content of boric acid is 34 g / L, and the content of nano powder is 90 g / L;

[0069] 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and is placed in an electrolyte with a distance of 20 mm between the anode and the cathode. Ultrasonic waves are applied to the electrolyte with a power of 1.6 kW and a frequency of 35 kHz. A pulse current is applied between the two electrodes with a current density of 3.5 A / dm and a pulse frequency of 2500 Hz. The pulse switching time in each pulse cycle is 2.2 ms and 60 ms respectively. The electrodeposition is performed for 140 min. The electrolyte temperature is controlled at 70°C during the electrodeposition process. After deposition, the cathode is removed for cleaning and drying to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

[0070] After testing, the thickness of the metal ceramic coating is 40μm, the relative density is 99.9%, the Vickers hardness HV is 565, the friction factor is 0.4, the thermal conductivity is 22W / m·K at 700K, and the bonding strength between the coating and the crystallizer copper plate substrate is 196MPa.

[0071] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a metal ceramic coating on the surface of a crystallizer copper plate by electrodeposition, characterized in that: The following steps are involved: 1) dissolving nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid in water, then adding nano powders, the nano powders comprising nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder, and uniformly dispersing by ultrasonic wave to obtain an electrolyte; 2) A nickel sheet is used as an anode and a crystallizer copper plate substrate is used as a cathode and placed in an electrolyte, ultrasonic waves are applied to the electrolyte, and a pulse current is applied between the two electrodes for electrodeposition. After deposition, the cathode is removed, cleaned and dried to obtain a crystallizer copper plate with a metal ceramic coating on the surface.

2. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: In the electrolyte, the content of nickel sulfate hexahydrate is 196-350 g / L, the content of nickel chloride hexahydrate is 42-88 g / L, the content of boric acid is 28-35 g / L, and the content of nano powder is 50-100 g / L.

3. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: In the nano powder, the mass ratio of nano nickel powder, nano alumina powder, nano silicon carbide powder and nano zirconium oxide powder is 3:(1-3):(1-3):(1-3).

4. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The purity of the nano nickel powder is greater than 99%, and the particle size is 3-10nm; the purity of the nano alumina powder is greater than 99.9%, and the particle size is 15-30nm; the purity of the nano silicon carbide powder is greater than 99.9%, and the particle size is 10-40nm; the purity of the nano zirconium oxide powder is greater than 99.9%, and the particle size is 5-10nm.

5. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: In step 2), the power of the ultrasonic wave is 1.5-1.8 kW, and the frequency is 30-40 kHz; the current density of the pulse current is 2-4 A / dm, the pulse frequency is 500-3000 Hz, and the pulse switching time in each pulse cycle is 0.5-3 ms and 20-80 ms respectively.

6. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The distance between the anode and the cathode is 15 to 25 mm; the electrolyte temperature is controlled to be 60 to 80° C. during the electrodeposition process; and the electrodeposition time is 80 to 150 minutes.

7. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The sum of the nickel and cobalt contents of the nickel sheet is ≥99.9%; the crystallizer copper plate matrix is ​​a Cu-Cr-Zr alloy or a Cu-Cr-Zr-Al alloy.

8. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The nickel sheet needs to be pre-treated before use, and the steps include: first, wiping the surface of the nickel sheet with deionized water and acetone repeatedly and alternately, then placing the nickel sheet in a mixed acid solution of nitric acid with a mass concentration of 60-70% and hydrochloric acid with a mass concentration of 36-40% in a mass ratio of 1:(6-8) to react for 1-5 minutes, taking it out and washing it with deionized water, and placing it in anhydrous ethanol for standby use.

9. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The crystallizer copper plate substrate needs to be pre-treated before use, and the steps include: firstly grinding the substrate surface with sandpaper, then ultrasonically cleaning the substrate in acetone at 50-55°C for 15-60 minutes, then ultrasonically cleaning the substrate in anhydrous ethanol at room temperature for 15-60 minutes, and then placing the substrate in anhydrous ethanol for standby use after cleaning.

10. The method for preparing the metal ceramic coating on the surface of the crystallizer copper plate by electrodeposition according to claim 1, characterized in that: The metal ceramic coating has a thickness of 5 to 50 μm, a relative density greater than 99.7%, a Vickers hardness HV of 350 to 600, a friction factor of 0.35 to 0.45, a thermal conductivity of 15 to 25 W / m·K at 700 K, and a bonding strength between the coating and the crystallizer copper plate substrate of 170 to 250 MPa.

Citation Information

Patent Citations

  • Method for preparing super-hydrophobic nickel / silicon carbide composite coating on metal surface

    CN109518238A

  • Supersonic-electrochemical deposition method for nano metal ceramics

    CN1557997A

  • Electrodeposition of metal coatings, preferably Ni or Cu, from electrolyte solutions containing hard particles, e.g. of corundum useful for ingot mold plates and continuous casting molds

    DE102005040151A1

Cited By

  • High-strength electroplated porous copper wick as well as preparation method and application thereof

    CN120311265A